Study of Modifying Lamb Muscle Protein Structure and Improving the Tenderness by Ultrasonic Treatment - Yuru YANG; Deyin PAN; Jinming MA; Xiaojuan JIANG; Hongsheng CHEN; Jingjing DIAO (Shipin gongye ke-ji, 2023)
In this study, the effects of ultrasonic treatment on the protein structure and quality characteristics of lamb were investigated using the ultrasonic time (0, 10, 20, 30, 40, 50 min) and power (0, 200, 250, 300, 350, 400 W) as variables. The results demonstrated that, with the extension of the ultrasonic time and power, the intensity of the Raman spectrum decreased and the α-helix content had a tendency to transform into β-fold. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis showed that ultrasonic treatment contributed to the dissociation of actomyosin. Scanning electron microscopy (SEM) exhibited that ultrasonic treatment enlarged the gaps among the muscle fiber bundles destroyed the muscle fiber structure of lamb, increased the myofibril fragmentation index (MFI) of lamb muscle, reduced shear force, and improved the water-holding capacity. According to all of the above indexes, the optimal ultrasonic conditions were determined: the ultrasonic power was 300 W for 30 min. In this condition, the MFI of lamb was 44.59, which was increased by 25.66% compared with the control group (P<0.05), and the shear force decreased to 31.22 N, which was 29.35% lower than the control group (P<0.05). The water-holding capacity was 93.59%. Therefore, the lamb was effectively tenderized under this ultrasonic condition.